Mengidentifikasi Masalah Yang ditemukan dalam Pengawasan Supervisi Pendidikan di Madrasah Tingkat Mts Kabupaten Langkat (International Forum of Researchers and Lecturers, 2024)
Researchers will discuss the problems found in the implementation of educational supervision in schools/madrasas. Educational supervision is an educational management process that aims to improve the quality of education through supervision, direction, and guidance of teachers or educators. Academic supervision is one of the scopes of educational supervision that aims to assist teachers in improving the quality of academic activities, both inside and outside the classroom. Researchers identified several problems faced by educational supervisors, such as the complexity of the principal's managerial tasks, the lack of preparation of the supervised teachers, the high element of subjectivity, the frequent changes of principals, the lack of teacher discipline, and the lack of teacher knowledge about managing an effective teaching and learning process. In addition, the quality of teachers in carrying out teaching tasks is also a challenge, as teachers often face difficulties in incorporating new innovations into learning. Researchers emphasize the importance of educational supervision in improving teacher performance and ultimately impacting on student learning outcomes. Therefore, efforts are needed to overcome the problems faced in implementing educational supervision, so as to improve teacher professionalism and the overall quality of education.